2008
DOI: 10.1016/j.ygeno.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide comparative phylogenetic and molecular evolutionary analysis of tubby-like protein family in Arabidopsis, rice, and poplar

Abstract: Tubby-like proteins, which are characterized by a highly conserved tubby domain, play an important role in the maintenance and function of neuronal cells during postdifferentiation and development in mammals. In additional to the tubby domain, most tubby-like proteins in plants also possess an F-box domain. Plants also appear to harbor a large number of TLP genes. To gain insight into how TLP genes evolved in plants, we conducted a comparative phylogenetic and molecular evolutionary analysis of the tubby-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 47 publications
7
58
1
Order By: Relevance
“…Boggon et al (1999) found that the Tubby protein is a bipartite transcription regulator and that its N-terminal segment is involved in modulating transcription. In plants, Tubby proteins contain a conserved F-box domain (Liu, 2008;Yang et al, 2008). Fbox proteins regulate diverse cellular processes, including cell cycle transition, transcriptional regulation, and signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Boggon et al (1999) found that the Tubby protein is a bipartite transcription regulator and that its N-terminal segment is involved in modulating transcription. In plants, Tubby proteins contain a conserved F-box domain (Liu, 2008;Yang et al, 2008). Fbox proteins regulate diverse cellular processes, including cell cycle transition, transcriptional regulation, and signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis-Piriformospora indica interaction [16][17][18] In Arabidopsis, AtTLP9 acts in ABA signaling during germination and plays a role in responses to salt and drought stress. 17,19 Consistent with this, a TLP from chickpea was recently demonstrated to confer increased tolerance to salt, drought and oxidative stress when overexpressed in tobacco.…”
Section: New Insights Into the Subcellular Localization Of Tubby-likementioning
confidence: 99%
“…23 Therefore, we fused GFP N-terminally to the Tubby domain of a barley (Hordeum vulgare) TLP (GenBank: AK251904.1) designated HvTLP12 for its similarity to rice TLP12. 18 The chimera (GFP-HvTLP12Δ1-123), was observed at the PM when expressed in Arabidopsis leaf epidermal cells (Fig. 3D).…”
mentioning
confidence: 97%
“…Tubby and Tubby-like proteins, which were initially linked to the spontaneous maturity-onset obesity syndrome in mice, were later shown to be involved in the development and functions of neuronal cells during post-differentiation in mice (Coleman and Eicher, 1990;Kleyn et al, 1996;Li et al, 2001;Ikeda et al, 2002;Yang et al, 2008). TULPs play crucial roles in photoreceptor degradation (Ikeda et al, 1999), embryonic lethality (Nishina et al, 1998) and membrane receptor trafficking (Mukhopadhyay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tubby proteins are highly conserved among different species of mammals, while TULPs are found in a wide range of multicellular organisms (Boggon et al, 1999;Lai et al, 2004). Tubby and TULPs are characterized by a conserved Tubby domain (approximately 270 amino acids) located at the C terminus (North et al, 1997;Yang et al, 2008;. The N-terminal region of Tubby proteins in humans is less conserved than the Cterminal region, suggesting that the C-terminal region is functionally redundant among the Tubby gene family members (Ikeda et al, 1999;Ikeda et al, 2001).…”
Section: Introductionmentioning
confidence: 99%